Impacts of technological shock on the agricultural business cycle - Jirawat Jaroensathapornkul, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The real business cycles in ASEAN-5 countries namely Indonesia, Malaysia, the Philippines, Thailand, and Vietnam over 1971-2015 fluctuated more than their agricultural business cycles. This research utilized the two-sector real business cycle model developed by Da-Rocha and Restuccia (2002) to stimulate such a stylized fact. The model assumes that a social planner makes a decision in an initial period to choose the consumption, capital stock, and working hours in the agricultural and non-agricultural sectors. This will enable a representative agent to attain optimum utility for the entire life under certain economic restrictions and subject to technology shocks occurring in both sectors. The mathematical methods applied to solve this decision-making problem for the social planner includes linear quadratic approximations and stochastic dynamic programming methods. The simulation results suggest that the applied model could reasonably well replicate the fluctuations of the real business cycle, agricultural business cycle, and the non-agricultural business cycle. This reflects the situation where technology shocks in the agricultural and non-agricultural sectors are related to each other and influence the volatility of these two economies.This suggest that the governments should encourage research and development activities in both agricultural and non-agricultural sectors to develop new technology that can generate technology shock to promote greater economic strength.